The Impact of a Vestibular-Stimulating Exercise Regime on Postural Stability in People with Visual Impairment - Wiszomirska, Ida (Biomed Res Int, 2015)
The aim of the study was to assess the impact of a vestibular-stimulating exercise regime on postural stability in individuals with visual impairment. The study group consisted of 70 people, including 28 persons (15 female and 13 male) with visual impairment and 42 (21 female and 21 male) without visual impairment. Each individual in the group with visual impairment was medically qualified for a 3-month training program. The research methodology included medical examination, anthropometric tests, and stabilometry tests on a Biodex Balance System SD (BBS). The tests were conducted twice: once before the start of training and again after 3 months of rehabilitation. The group with visual impairment showed significantly worse postural stability results than the control group for most of the stability parameters evaluated (OSI, APSI, and MLSI). Differences were noted between the groups with and without visual impairment for dynamic tests in women and for static tests in men. After training, the two groups showed roughly similar results for the stabilometry test with eyes closed. We conclude that exercises stimulating the vestibular system with head and body movements should be recommended for individuals with visual impairments to achieve better balance retention.